Creation of Plastic Marble - Huriya, Syeda Saba; Ganesh, R.; Ravali; Sandhya; Fahad (International Journal of Scientific Research in Civil Engineering, 2018)
Plastics are polymers and environmentally, a growing disaster. Daily, millions of new plastic bags are manufactured and used by us in our day-to-day life in the form of carry bags, wrapping the objects etc. But disposal of plastic wastes leads to many hazards causing harm to environment as well as life. Most of the plastics are non-biodegradable and lasts for decades may be centuries and thus, making it difficult to dispose. So best way is either to recycle or reuse them for other purposes. By reusing the plastic, we are going to create a marble or marble like objects which will be super strong but not as much as natural marbles which exists. So the procedure follows, firstly we collect different kinds of plastic bags made from ADPE and HDPE etc. After separating them, it is shredded in the shredder or can normally be cut into small pieces. Then later it is heated(or)burned at certain temperature, and compression, moulding etc. Procedures are carried out step by step lastly forming it into a fine marble. At last, finally obtained marble surfaces are made smooth and polished before using them for various purposes. The sustainable way of treating plastic waste is as a resource so, In this way plastic bags can be reused in manufacturing different things which are required in our daily life.